MORPHOLOGICAL CRITERIA OF THE THYMUS IN CONGENITAL HEART DISEASE - Komiljonova Oygul Olimjonovna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
The thymus is the central organ of immunogenesis, determining the state of the immune system of any subject, especially in childhood. Consequently, morphological shifts in the structure of the thymus are the basis for solving the problem of a defect in the immune system. In children with congenital heart disease, pronounced morphological changes in the structure of the thymus were noted, affecting the differentiation of T lymphocytes and disrupting their subpopulation ratio.